Empire or multilateralism? - Cordovez, Diego (2016)
This article reviews the main events surrounding the U.S. attack on Iraq. It also analyzes the position assumed by the US. at the UN Security Council, proposing a debate within this organization aimed at defining its role in the new inter-national context. Finally, the author explores the Middle East situation, examining the possibilities of success of the "route map': and reviews the main events in Latin America.